Financial behavior as a mediating influence of financial knowledge on financial distress in millennial generation in candi subdistrict, sidoarjo district - Lestari, Ardya Putri; Zaki, Achmad (Enrichment : Journal of Management, 2023)
Financial management is very important for all groups, including the millennial generation who have minimal income because they are still in school to avoid consumptive purchases and financial distress. The purpose of this study is tiio gaiiin a deeper understanding of financial behavior as a mediiiating iiinfluence oiif financiiial knowledge on financial distress among the younger generation living in the temple sub-district of Sidoarjo city. This research can be classified as quantitative research using the path analysis method. The data collection technique used is a questionnaire using a Likert scale as the basis for measurement. The population of this study were adolescents in the temple sub-district aged 10-18 years. To determine the sample used non-probability sampling, and the sampling method used Accidental Sampling. The sample size studied was 80 respondents. The results showed that the financiiial knowledge variable had a negative and significant effect oiin financiiial distress, the financiiial kiinowledge variable had a positive and significant effect on financial behavior, and the financial behavior variiiable had a positive and significant effect oiin financial distress. The relationship between intervening variables shows tiihat financiiial behavior has a positive and significant effect in mediating financiiial knowledge on financial distress in financial management.